Colony-stimulating factor 1 receptor (CSF1R) inhibitors in cancer therapy. Issue 1 (18th July 2017) - Cannarile, Michael A.; Weisser, Martin; Jacob, Wolfgang; Jegg, Anna-Maria; Ries, Carola H.; Rüttinger, Dominik
Abstract : The tumor-permissive and immunosuppressive characteristics of tumor-associated macrophages (TAM) have fueled interest in therapeutically targeting these cells. In this context, the colony-stimulating factor 1 (CSF1)/colony-stimulating factor 1 receptor (CSF1R) axis has gained the most attention, and various approaches targeting either the ligands or the receptor are currently in clinical development. Emerging data on the tolerability of CSF1/CSF1R-targeting agents suggest a favorable safety profile, making them attractive combination partners for both standard treatment modalities and immunotherapeutic agents. The specificity of these agents and their potent blocking activity has been substantiated by impressive response rates in diffuse-type tenosynovial giant cell tumors, a benign connective tissue disorder driven by CSF1 in an autocrine fashion. In the malignant disease setting, data on the clinical activity of immunotherapy combinations with CSF1/CSF1R-targeting agents are pending. As our knowledge of macrophage biology expands, it becomes apparent that the complex phenotypic and functional properties of macrophages are heavily influenced by a continuum of survival, differentiation, recruitment, and polarization signals within their specific tissue environment. Thus, the role of macrophages in regulating tumorigenesis and the impact of depleting and/or reprogramming TAM as therapeutic approaches for cancer patients may vary greatly depending on organ-specific characteristics of these cells. We review the currently available clinical safety and efficacy data with CSF1/CSF1R-targeting agents and provide a comprehensive overview of ongoing clinical studies. Furthermore, we discuss the local tissue macrophage and tumor-type specificities and their potential impact on CSF1/CSF1R-targeting treatment strategies for the future.